2002
DOI: 10.1007/s00330-002-1628-3
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-containing contrast media for radiographic examinations: a position paper

Abstract: Recently, it has been suggested that gadolinium-based contrast media could be used for radiological examinations in patients with significant renal impairment, previous severe generalized reaction to iodinated contrast media or thyroid disease about to undergo radioactive iodine treatment; however, the indications for and risks of using gadolinium agents in this way are not well known; hence, the Contrast Media Safety Committee of The European Society of Urogenital Radiology reviewed the literature to issue a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(40 citation statements)
references
References 27 publications
(29 reference statements)
0
35
0
4
Order By: Relevance
“…These agents have similar biodistributions, pharmacokinetics and half-lives [1][2][3][4][5]. The biologic elimination of half-life of these agents is approximately 1.5 h; the plasma half-life increases in relation to the degree of renal insufficiency.…”
Section: Gadolinium Preparations and Pharmacokineticsmentioning
confidence: 96%
“…These agents have similar biodistributions, pharmacokinetics and half-lives [1][2][3][4][5]. The biologic elimination of half-life of these agents is approximately 1.5 h; the plasma half-life increases in relation to the degree of renal insufficiency.…”
Section: Gadolinium Preparations and Pharmacokineticsmentioning
confidence: 96%
“…However, it was a previous misconception that the use of GDBCA was safe in patients with underlying renal insufficiency [2]. The Contrast Media Safety Committee (CMSC) of the European Society of Urogenital Radiology (ESUR) did not approve GDBCA for radiographic examinations [3]. It was stated that GDBCA should not be used for radiographic examinations in patients with renal impairment and that these contrast agents are more nephrotoxic than iodinated contrast in equivalent radiographic attenuating doses.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, gadolinium-based contrast agents (GDBCA) were used as alternative contrast agents for conventional angiography in patients with renal insufficiency on an off-label basis, although the Contrast Media Safety Committee (CMSC) of the European Society of Urogenital Radiology (ESUR) did not approve GDBCA for radiographic examinations [2,3]. In a previous study, it was concluded that angiography and percutaneous treatment of renal artery stenosis in patients with chronic renal insufficiency and suspected ischaemic nephropathy can be performed safely using intra-arterial injections of GDBCA as contrast media without an increased risk of complications.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, it was widely believed that the gadolinium based contrast media used for Magnetic resonance imaging (MRI) were not nephrotoxic and they were used for conventional angiography and some CT studies to protect the poorly functioning kidney from the nephrotoxicity of iodine based contrast media [11,12]. However, the nephrotoxic potential of the gadolinium based agents is now recognized [13,14].…”
Section: Contrast Induced Nephropathy (Cin))mentioning
confidence: 99%